Potable Water Quality Assessment from Local Restaurants: Study from South Central Coastal District of Bangladesh - Khan, Md. Shohel; Farha, Mahmuda (Journal of Asian Scientific Research, 2022)
This study was conducted to measure physiochemical, i.e., pH, Electrical Conductivity (EC), Total Dissolved Solid (TDS), Chloride (Cl-), Iron (Fe2+), Sulphate (SO42-) and microbial parameters, like Total Viable Bacteria Count (TVBC), Total Coliform Count (TCC), Fecal Coliform (FC), Salmonella spp. and Vibrio spp. for suitability of drinking water of local restaurants in Noakhali. Total 18 samples were collected from six sampling stations, i.e., Noakhali Science and Technology University Campus (NSTU), Sonapur, Maijdee, Chowrasta, Chowmuhani and Sonaimuri, respectively. The result revealed that pH, EC, TDS, Fe2+, Cl- and SO42- were ranged from 7.19-8.47, 250-6710µs/cm, 130-370mg/l, 0.03-0.15mg/l, 46.79-2602.03mg/l, and 7.01-54.67mg/l, with the mean of 7.61, 2097.78µs/cm, 1077.22mg/l, 0.0566mg/l, 684.03mg/l and 15.40mg/l, respectively. The TVBC, TCC, FC, Salmonella spp. and Vibrio spp. were ranged from 4×104-1.81×105 cfu/100ml, 4×103-1.67×105 cfu/100ml, 0-9.2×104 cfu/100ml, 0-1.6×104 cfu/100ml, respectively but Vibrio spp. were totally absent throughout the study. The correlation between physicochemical and microbial parameters were strongly positive with TDS:EC (r=0.997), EC:Cl- (r=0.930), TDS:Cl- (r=0.929) at 0.05 level of significance and significant negative correlation between pH:EC (r=-0.563), TDS:pH (r= -0.577), SO42-:pH (r=-0.449), respectively but TVBC and TC were positively (r=0.499) correlated. The study concluded that almost all water samples were contaminated by microbial contamination and all the result of physicochemical parameters were not suitable for consumption that might be a negative impact on human health.